Immaculate conceptions: Micro-CT analysis of diagenesis in Romano-British infant skeletons. (October 2016) - Booth, Thomas J.; Redfern, Rebecca C.; Gowland, Rebecca L.
Abstract: Most histological analyses of bone diagenesis are destructive and limited to the inspection of a cross-section that may not be representative of the whole. X-ray microtomography (Micro-CT) may provide a non-destructive means of investigating taphonomically-significant diagenetic alterations throughout whole bone samples, but this method has not been tested systematically (Dal Sasso et al., 2014). Bacterial bioerosion is the most common form of diagenesis found in archaeological bones, yet a recent large-scale study of European archaeological human bones found that an unusually high proportion of young infant (<1 month old) samples were free from bacterial attack (Booth, 2016 ). This result is best explained by the remains of stillborn or short-lived infants who had died before their osteolytic gut bacteria had developed. The ability to differentiate between stillborn and short-lived infants would profoundly impact on the study of past human life courses and the study of infanticide in both archaeological and forensic contexts. In this study we investigate the efficacy of micro-CT in studying bone diagenesis by scanning three archaeological human femoral samples where levels of diagenesis are known and varied, before scanning a novel sample set of ten Romano-British young infant/perinatal femora to test the dichotomous appearance of bioerosion. We find that micro-CT is a viable non-destructive method of investigating bone bioerosion, but is less useful for characterising diagenetic staining and inclusions. Half of the infant samples studied here were free from bacterial bioerosion, further suggesting that histological analysis can be used to identify archaeological remains of stillborn and short-lived infants. Highlights: Systematic assessment of micro-CT as a method for investigating bone diagenesis. Bones with known levels of diagenesis and a novel sample of Romano-British infant skeletons are micro-CT scanned. Results suggest Micro-CT is a viable non-destructive method of investigating bacterial bioerosion throughout a bone volume. High preservation of infant samples suggests that histological techniques can identify stillborn infants.